2021
DOI: 10.3390/genes12070970
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Long Non-Coding RNAs in Trophoblast Regulation in Preeclampsia and Intrauterine Growth Restriction

Abstract: Preeclampsia (PE) and Intrauterine Growth Restriction (IUGR) are two pregnancy-specific placental disorders with high maternal, fetal, and neonatal morbidity and mortality rates worldwide. The identification biomarkers involved in the dysregulation of PE and IUGR are fundamental for developing new strategies for early detection and management of these pregnancy pathologies. Several studies have demonstrated the importance of long non-coding RNAs (lncRNAs) as essential regulators of many biological processes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 157 publications
(178 reference statements)
0
9
0
Order By: Relevance
“…The same analysis uncovered that 40.6% (84/207) of ecDNAs overlapped with the coordinates of 1288 unique lncRNAs, 20.8% (43/207) of ecDNAs overlapped coordinates of 184 unique miRNAs, and 14.9% (31/207) of ecDNAs overlapped coordinates of 57 unique snoRNAs (Supplementary Data 11B). The results indicate that the function of these cyclic elements may be associated with lncRNA, tRNA, miRNA, snoRNA, etc., and some studies have demonstrated that under the conditions of stress, the expression of ncRNAs may change and participate in the progression of FGR (32,33).…”
Section: Biological Function Of Eccdnas/ecdnasmentioning
confidence: 99%
“…The same analysis uncovered that 40.6% (84/207) of ecDNAs overlapped with the coordinates of 1288 unique lncRNAs, 20.8% (43/207) of ecDNAs overlapped coordinates of 184 unique miRNAs, and 14.9% (31/207) of ecDNAs overlapped coordinates of 57 unique snoRNAs (Supplementary Data 11B). The results indicate that the function of these cyclic elements may be associated with lncRNA, tRNA, miRNA, snoRNA, etc., and some studies have demonstrated that under the conditions of stress, the expression of ncRNAs may change and participate in the progression of FGR (32,33).…”
Section: Biological Function Of Eccdnas/ecdnasmentioning
confidence: 99%
“…Several studies have investigated the role of lncRNAs in the pathogenesis of preeclampsia throughout their function in trophoblast migration, proliferation, and invasion [ 11 ]. The lncRNA UCA1 has been widely studied in cancer samples [ 30 , 31 ] and in trophoblast cells [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the essential regulatory roles of lncRNA in preeclampsia [ 11 ]. Many differentially expressed lncRNAs in the placentas of preeclamptic patients have been reported, which suggests the potential role of lncRNAs in the pathogenesis of preeclampsia and their function in trophoblast cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) bear great responsibility for the occurrence and development of preeclampsia through modulation on the biological functions of trophoblasts, immune regulation, and epigenetic regulation [6–8]. Our bioinformatics analyses discovered TLR8-AS1 as a potential preeclampsia associated lncRNA.…”
Section: Introductionmentioning
confidence: 91%